Hubungan Tingkat Pengetahuan Ibu dengan Praktik Penatalaksanaan Diare pada Balita - Utami, Rosiana Putri; Wurjanto, Moh. Arie; Martini, Martini (Jurnal Riset Kesehatan Masyarakat, 2022)
Abstract: Diarrhea is a disease that occurs when a person has at least three loose stools per day. Diarrhea is considered a mild disease, but it can be fatal if not treated properly, especially in toddlers and children. The involvement of the mother in the management of diarrhea in toddlers is necessary. The aim of this study is to study the relationship between mother’s knowledge and diarrhea management practices in toddler in the Working Area of Puskesmas Sumowono, Semarang Regency. In this study focused on observational analytical studies using cross-sectional design. This study’s sample size was 122 respondents. The univariate test findings showed that the majority of respondents (54,1%) are high school graduates, 59,8% have adequate knowledge, and 59,8% have good practices for managing with diarrhea in toddlers. The bivariate analysis discovered a correlation between mother’s knowledge and diarrhea management practices (p=0.000). The most of respondents had sufficient knowledge and practice (74,0%). Keywords: Mothers’s knowledge, toddler diarrhea, diarrhea management